Beta-adrenergic agonists, ractopamine hydrochloride and salbutamol, as performance enhancers in the finisher pig - Jansen van Rensburg, Christine (University of Pretoria, 2025)
Dissertation (MSc Agric (Animal Science Animal Nutrition ))--University of Pretoria, 2025.